Spiro [fluorene-9,9 '-xanthene]-containing copolymers of intrinsic microporosity: synthesis, characterization and gas permeation properties - Shrimant, Bharat; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2018)
In the present study, a new bis(catechol) containing spiro[fluorene-9,9'-xanthene], namely, 4,4'-(spiro(fluorene9,9'-xanthene]-2',7'-diyl)bis(benzene-1,2-diol) (THSFX) was designed and synthesized. Polycondensation reactions of THSFX and varying compositions of THSFX and 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobisindane (TTSBI) were carried out with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain a homopolymer and copolymers, respectively. The organo-soluble polymers exhibited reasonably high molecular weights (23300-34,100 g/mol) and could be cast into self-standing films from their chloroform solutions. X-Ray diffraction studies indicated that PIMs were amorphous in nature. These polymers exhibited high thermal stability (T-10 = 490-510 degrees C) and possessed intrinsic microporosity with high BET surface area (360-796 m(2)/g). The gas permeation properties of SFX-PIM-25 and SFX-PIM-33 were evaluated and they exhibited high gas permeability (CO2 = 3595-4034 Barrer). The gas permeability data of SFX-PIM-25 and SFX-PIM-33 was located close to 1991 Robson upper bound for CO2/N-2, CO2/CH4 and O-2/N-2 gas pairs

Synthesis, characterization, and gas permeation properties of adamantane-containing polymers of intrinsic microporosity - Shrimant, Bharat; Shaligram, Sayali V.; Kharul, Ulhas K.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2018)
A new bis(catechol) monomer, namely, 4,4-((1r,3r)-adamantane-2,2-diyl)bis(benzene-1,2diol) (THADM) was synthesized by condensation of 2-adamantanone with veratrole followed by demethylation of the formed (1r,3r)-2,2-bis(3,4 dimethoxyphenyl)adamantane. Polycondensation of THADM and various compositions of THADM and 5,5,6,6-tetrahydroxy-3,3,3,3-tetramethylspirobisindane was performed with 2,3,5,6-tetrafluoroterephthalonitrile (TFTPN) to obtain the homopolymer and copolymers. These polymers demonstrated good solubility in common organic solvents such as dichloromethane, chloroform, and tetrahydrofuran and could be cast into tough films from their chloroform solutions. GPC analysis revealed that number average molecular weights of polymers were in the range 48,100-61,700 gmol(-1), suggesting the formation of reasonably high molecular weight polymers. They possessed intrinsic microporosity with Brunauer-Emmett-Teller (BET) surface area in the range 703-741 m(2)g(-1). Thermogravimetric analysis of polymers indicated that 10% weight loss temperature was in the range 513-518 degrees C demonstrating their excellent thermal stability. THADM-based polymer of intrinsic microporosity (PIM) showed P(CO2)=1080, P(O-2)=232 and appreciable selectivity [(CO2/CH4)=22.6, (CO2/N-2)=26.7, and (O-2/N-2)= 5.7]. The gas permeability measurements revealed that with increase in the content of adamantane units in PIMs, selectivity increased and permeability decreased, following the trade-off relationship. The gas separation properties of PIMs containing adamantane units were located close to 2008 Robeson upper bound for gas pairs such as CO2/CH4, CO2/N-2, H-2/N-2, and O-2/N-2. (c) 2017 Wiley Periodicals, Inc.
Keywords: adamantane; Gas permeation; intrinsic microporosity; membranes; structure-property relations